Navigating the Challenges of Oesophageal Atresia With Tracheo-Oesophageal Fistula: A Case-Based Review From Diagnosis to Recovery - Harridas Manickam; Azliana Aziz; Mohd Shahrulsalam Mohd Shah (Malaysian Journal of Paediatrics and Child Health, 2026)
Oesophageal atresia with distal tracheo-oesophageal fistula (Type C EA/TEF) is the most common anatomical subtype of EA/TEF and requires early diagnosis and surgical management. Delayed recognition increases the risk of aspiration-related complications. This report describes the presentation, multidisciplinary management and early postoperative outcomes of two neonates with Type C EA/TEF treated at a tertiary referral centre. Two neonates presented after birth with respiratory distress, excessive oral secretions or feeding difficulty, and failed nasogastric tube passage. Radiographs demonstrated coiling of the nasogastric tube in the proximal oesophageal pouch with gastric air, consistent with Type C EA/TEF. Both underwent preoperative bronchoscopy followed by right thoracotomy, fistula ligation and primary oesophageal anastomosis. Postoperative contrast studies showed intact anastomoses without leakage, oral feeding was established, and both infants were discharged in good condition. At 1-month follow-up, both were feeding well and gaining weight without respiratory symptoms. These cases emphasise early clinical suspicion, systematic assessment for associated anomalies and coordinated multidisciplinary care. They also illustrate that early recognition does not necessarily equate to immediate interhospital transfer. Both infants had favourable documented outcomes at 1-month follow-up.